Sociopolitical Dimensions of English in Nepal - Upadhyay, Hriseekesh (The Harvest, 2023)
Nepal is an English as a Foreign Language (EFL) country where teaching and learning of English was disallowed under the Ranas for political reason while English took root in the rest of South Asia under the British colonial dispensation for over two centuries. English was adopted as a useful tool to enhance Nepal’s standing and to strengthen its relations with the outside world after the Ranas were removed from ower in 1951. This research paper dwells on how choosing English for use in a nation for education, business and foreign relations constitutes a political act and how Nepal’s political history guided the resistance to use English in the nation and how the changed political scenario pushed the country to adopt teaching and learning of English in a big way. Political thinking even determines how the choice of English is described at the official level to camouflage it as a purely nationalistic invention dubbing it as one of the U.N. languages which Nepal as a member must master to play its role in the world body. This research paper seeks to highlight the context of EFL in Nepal in the past fifty years, describes the modes of teaching and learning of English in the country and tries to demonstrate that English in Nepal does not fall under the nstitutionalized variety of English such as Indian or South Asian English.